Preterm premature rupture of membranes at 32–34 weeks of gestation: duration of membrane rupture period and maternal blood indicators relation with congenital infection - Daunoravičienė, Ieva; Lenkutienė, Rūta; Musteikytė, Audrė; Ramašauskaitė, Diana (Acta medica Lituanica, 2015)
Background. The study investigates the influence of the length of membrane rupture period among pregnant women with preterm premature rupture of membranes (PPROM) between the 32nd and 34th weeks of gestation on the development of chorioamnionitis and the congenital infection of a newborn. It seeks to ascertain the values of indicators in mother’s blood that enable to predict chorioamnionitis and funisitis for mothers, and congenital infection for newborns. Materials and methods. A retrospective study of case records of women with PPROM at 32 (32 w. + 0 d)–34 (33 w. + 6 d) weeks of gestation and their newborns was performed. Two comparative groups were made: 1) of women who had funisitis and / or chorioamnionitis with or without deciduitis and 2) of women having no proved inflammation (according to the results of histological examination of placentae). Analogically, comparative groups were made of their newborns: those who had diagnosis of congenital infection and those who had no infection. The duration of membrane rupture period and the blood markers were investigated in all the groups. Results. The study included 135 women. Duration of the membrane rupture period lasted 85.17 ± 84.72 hrs in the group of women who had histological inflammation, and 40.06 ± 56.57 hrs in the group with no inflammation, P = 0.01, AUC = 0.735; the critical membrane rupture period value for developing intrauterine infection by the Youden index was 43.7 hrs. The corresponding maternal CRP values (mg/l) were 25.85 ± 40.27 vs. 5.23 ± 7.88 (P = 0.01, AUC = 0.6), the Youden index 4.6 mg/l. For the mothers of the newborns diagnosed with infection, the duration of the membrane rupture period was 55.95 ± 65.04 hrs, for the mothers of the newborns without congenital infection it was 40.25 ± 73.71 hours. Respectively, CRP values for the mothers of newborns averaged 12.25 ± 22.14 mg/l vs. 4.8 ± 4.82 mg/l (P = 0.005). Conclusions. Longer membrane rupture period and higher maternal CRP are correlated with inflammatory changes in the placenta and umbilical cord, thus they can be used as the prognostic indicators of intrauterine infection. When the duration of the membrane rupture period lasts ≥44 hrs, the risk of chorioamnionitis and funisitis increases five times; when the maternal serum CRP is higher than 5 mg/l, funisitis / chorioamnionitis is twice more frequent than at lower than 5 mg/l CRP values.